Effects of executive function training on balance and auditory-cognitive dual-task performance in adults with and without hearing loss - Niroshica Mohanathas; Lianna Montanari; Rachel Downey; Karen Z. H. Li; Margaret Kathleen Pichora-Fuller; Louis Bherer; Maxime Lussier; Natalie Phillips; Walter Wittich; Nancy St-Onge; Jean-Pierre Gagne; Jennifer L. Campos (PLoS ONE, 2026)
Background Multitasking, such as listening while balancing, relies on integrated processing in the sensory, cognitive, and motor systems; systems that often decline with age. Hearing loss is linked to increased risks of both falls and cognitive decline. Improving cognitive processing through executive function (EF) training may support balance, especially in older adults with hearing loss. This randomized controlled study conducted across age groups and hearing abilities, examined the effects of a 12-week EF training program on postural outcomes (center of pressure (COP)) using an auditory-cognitive-postural dual-task paradigm. Methods Sixty-five participants including middle-aged adults with normal hearing (MA; n = 19), older adults with normal hearing (OA; n = 23), and older adults with hearing loss who used hearing aids (OAHL; n = 23) were randomly assigned within each age group to an EF training condition or a control condition. Primary outcome measures were auditory-cognitive reaction time on an auditory 2-back working memory task and postural measures (COP path length variability), which were collected in single- and dual-task conditions. Secondary analyses examined whether sensory, cognitive, and mobility performance, as evaluated by baseline standardized assessments, predicted training-related outcomes. Results Across MA, OA, and OAHL groups, cognitive performance generally improved following EF training and transfer of these training effects were observed during experimental postural tasks and auditory-cognitive tasks, but differed depending on age, pure-tone hearing thresholds, and cognitive abilities. Specifically, for postural outcomes, performance improved after training, but only for older adults with better hearing, while those with poorer hearing at any age did not improve. For auditory-cognitive task performance, older adults with the poorest hearing and cognition benefited the most from training. Conclusions EF training may support balance and cognition in older adults, although its benefits for balance may be limited by severe hearing loss, underscoring the value of early intervention. Trial registration Registry Name: ClinicalTrials.gov. Registration/Trial number: NCT05418998. Trial URL: https://clinicaltrials.gov/ct2/show/NCT05418998 .